Literature Review on Political Communication Practices in the Digital Age - Jauza Alayya (Budapest International Research and Critics University, 2022)
New media and technology have changed interpersonal interactions, communication patterns, and even socio-political discussions. Not only bringing change, in its development technological advances, especially digital media, also play an important role in democratic activities and political communication. By using a simple literature review, this article will attempt to present the development of political communication practices on social media and their implications for the dynamics of political communication. The findings show that the use of social media in political communication activities is not a new trend and its significance continues to increase over time. In addition, the use of social media in political communication has proven to be successful in providing benefits for both political actors and the public. However, the use of social media in political communication also presents other concerns, namely the phenomenon of black campaigns, the spread of hoaxes, hate speech, to polarization that require special attention and handling.